The Relationship Between The Role of Parents, Friends and Religiousness to Sexual Behavior in Adolescents at State Islamic Boarding Schools in Tebing Tinggi - Fakhreni Fakhreni; Delfriana Ayu Astuty; Salianto Salianto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The World Health Organization (WHO) estimates that 4,2 million abortions are perfomed each year and between 750,000 and 1,5 million occur in Indonesia.Adolescents in Indonesia have been shown to start having sex at a young age,this is evident from several studies which show that the ages of 14-23 years and continues to increase every year. The purpose of this study was to determibe whether there is a relationship between the role of parents,peers and religiosty on adolescent sexual behavior in .This type of research is non-experimental observational using a cross sectional approach.The instrument used in this study using simple sampling techniques.The population in this study was a questionnaire distributed to respondents.In this study using simple sampling techniques.The population in this study amounted to 132 people and the sample size taken was 57 people who were surveyed directly.Random sampling of 10th and 11 th grade students.This study uses spearman statistical analysis.The results showeed that the role of parents on sexual behavior was (p=0.743, r= 0.44),peers on sexual behavior was (p= 0.027, r= 0.293) and religiosity on sexual behavior was (p=0.714, r=0,050) on the peer role variable there was a relationship with a significant value of the strength of the relationship of 0,0361,meaning that peers and sexual behavior have a perfect negative linear correlation (p-value= 0,006) or below 0.05 which means that at 5% alpha indicates that there is a relationship between the role of parents and religious understanding in adolescents,the less likely adolescents are to behave sexually.Sugestions to prevent adolescents in unhealthy associations,it is important for adolescents to morals with religious knowledge,as well as create and maintain good communication relationship with parents,so as not to fall into the wrong association and be more able to choose good friendships and bring themselves not to fall into unwanted negativity. Keywords: Adolescents, Parents, Peers, Religiousness, Sexual Behavior